Online Instrument of Elementary School Teacher’s Perfomance Assessment - Yuniarti, Siska Indria; Dwikurnaningsih, Yari (Journal of Education Technology, 2022)
The problem that occurs at this time is that the current teacher performance assessment instrument does not accommodate assessments in elementary schools related to their main tasks and functions. This research aims to develop a teacher performance assessment instrument based on the basic tasks and function of elementary-school teachers online. The research was developed in a research method and development based on the borg and gall development model until step five. Through research and development this is done to design and develop teacher performance assessment instruments according to the peripheral assignment and primary school teacher's function and according to the mission's vision online. The collection of data in this study involves qualitative and quantitative methods. The subject of this research is superintendent, principal and elementary school teacher. The application used to develop this instrument is MySQL. The development of this teacher's performance assessment instrument results in six basic teacher duties and functions as ministers of faith, spiritual leaders, academic leaders, biblical role models, mentors, and character educators. The data analysis uses miles and hubermans through data reduction, presentation and drawing conclusions. Based on analysis of the validity by the teacher performance assessment expert gained a 93.3% score and is categorized perfectly feasible. Whereas the results of the validity by the expert on it acquired a score of 90.7% in highly deserved category. Product trials by supervisors, headmasters and teachers produced a 92% score in the highly viable category,so the product of developing these elective teacher performance assessment tools online can be used.